Life in a fragment: Evolution of foraging strategies of translocated collared brown lemurs, Eulemur collaris, over an 18‐year period. Issue 4 (18th February 2020) - Donati, Giuseppe; Campera, Marco; Balestri, Michela; Barresi, Marta; Kesch, Kristina; Ndremifidy, Kelard; Rabenantoandro, Jonhy; Racevska, Elena; Randriatafika, Faly; Ravaolahy, Murielle; Ravoahangy, Andriamandranto M.; Roma, Marika; et al.
Abstract: While the drivers of primate persistence in forest fragments have been often considered at the population level, the strategies to persist in these habitats have been little investigated at the individual or group level. Considering the rapid variation of fragment characteristics over time, longitudinal data on primates living in fragmented habitats are necessary to understand the key elements for their persistence. Since translocated animals have to cope with unfamiliar areas and face unknown fluctuations in food abundance, they offer the opportunity to study the factors contributing to successful migration between fragments. Here, we illustrated the evolution of the foraging strategies of translocated collared brown lemurs ( Eulemur collaris ) over an 18‐year period in the Mandena Conservation Zone, south‐east Madagascar. Our aim was to explore the ability of these frugivorous lemurs to adjust to recently colonized fragmented forests. Although the lemurs remained mainly frugivorous throughout the study period, over the years we identified a reduction in the consumption of leaves and exotic/pioneer plant species. These adjustments were expected in frugivorous primates living in a degraded area, but we hypothesize that they may also reflect the initial need to cope with an unfamiliar environment after the translocation. Since fragmentation is often associated with the loss of large trees and native vegetation, we suggest that the availability of exotic and/or pioneer plant species can provide an easy‐to‐access, nonseasonal food resource and be a key factor for persistence during the initial stage of the recolonization. Abstract : An adult male of collared brown lemur, Eulemur collaris, resting in the Mandena littoral forest (credit: Jennifer Chambler). Research Highlights: Collared brown lemurs remained mainly frugivorous over a 18‐year period after their translocation into a new forest fragment. Exotic and pioneer plant species facilitate persistence during the initial stage of the recolonization.